Characterisation and use of biomass fly ash in cement-based materials - Rajamma, Rejini
This paper presents results about the characterisation of the biomass fly ashes sourced from a thermal power plant and from a co-generation power plant located in Portugal, and the study of new cement formulations incorporated with the biomass fly ashes. The study includes a comparative analysis of the phase formation, setting and mechanical behaviour of the new cement–fly ash formulations based on these biomass fly ashes. Techniques such as X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), thermal gravimetric and differential thermal analysis (TG/DTA), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and environmental scanning electron spectroscopy (ESEM) were used to determine the structure and composition of the formulations. Fly ash F1 from the thermal power plant contained levels of SiO2, Al2O3 and Fe2O3 indicating the possibility of exhibiting pozzolanic properties. Fly ash F2 from the co-generation plant contained a higher quantity of CaO (∼25%). The fly ashes are similar to class C fly ashes according to EN 450 on the basis of chemical composition. The hydration rate and phase formation are greatly dependant on the samples’ alkali content and water to binder (w/b) ratio. In cement based mortar with 10% fly ash the basic strength was maintained, however, when 20% fly ash was added the mechanical strength was around 75% of the reference cement mortar. The fly ashes contained significant levels of chloride and sulphate and it is suggested that the performance of fly ash–cement binders could be improved by the removal or control of these chemical species.